TRANSFORMASI DIGITAL LAYANAN PENDAFTARAN ANGGOTA CREDIT UNION MELALUI SISTEM BERBASIS WEB - Ratna Sari; Iip Yulianto Windra (Universitas Citra Bangsa, 2026)
Credit Union Keling Kumang Branch Office Pasar Sekadau (hereinafter referred to as CU Keling Kumang BO Pasar Sekadau) is a financial institution that continues to grow. The development of a web-based new member registration application to improve services by replacing manual registration so that problems of validation delays, file accumulation and input errors can be overcome. It is hoped that with the web-based registration process, members will become easier, more flexible and more efficient. The method used in the design is Waterfall, which includes the stages of needs analysis, design, implementation, testing and maintenance. The implementation results show that the web-based registration application is able to facilitate new member registration quickly, accurately and transparently. The presence of an automatic data verification feature and integration with the internal database of CU Keling Kumang BO Pasar Sekadau minimizes input errors and speeds up the validation process. Based on the results of testing using analysis usability with average score 77 and interviews with CU Keling Kumang BO Pasar Sekadau staff, the system has been proven to increase efficiency compared to manual registration, users can use the application quite easily and has received positive responses from users due to its ease of access, simple interface and the availability of registration status notifications. The implementation of the new member registration application for CU Keling Kumang BO Pasar Sekadau can be an effective solution to support the digital transformation of community-based financial institutions, especially at CU Keling Kumang BO Pasar Sekadau.